Compliance with and effectiveness of adaptive servoventilation versus continuous positive airway pressure in the treatment of Cheyne-Stokes respiration in heart failure over a six month period. Issue 3 (17th June 2005) - Philippe, C; Stoïca-Herman, M; Drouot, X; Raffestin, B; Escourrou, P; Hittinger, L; Michel, P-L; Rouault, S; d'Ortho, M-P
Abstract : Objective: To compare compliance with and effectiveness of adaptive servoventilation (ASV) versus continuous positive airway pressure (CPAP) in patients with the central sleep apnoea syndrome (CSA) with Cheyne-Stokes respiration (CSR) and with congestive heart failure in terms of the apnoea–hypopnoea index (AHI), quality of life, and left ventricular ejection fraction (LVEF) over six months. Methods: 25 patients (age 28–80 years, New York Heart Association (NYHA) class II–IV) with stable congestive heart failure and CSA-CSR were randomly assigned to either CPAP or ASV. At inclusion, both groups were comparable for NYHA class, LVEF, medical treatment, body mass index, and CSA-CSR. Results: Both ASV and CPAP decreased the AHI but, noticeably, only ASV completely corrected CSA-CSR, with AHI below 10/h. At three months, compliance was comparable between ASV and CPAP; however, at six months compliance with CPAP was significantly less than with ASV. At six months, the improvement in quality of life was higher with ASV and only ASV induced a significant increase in LVEF. Conclusion: These results suggest that patients with CSA-CSR may receive greater benefit from treatment with ASV than with CPAP.